THE EFFECT OF FINANCING RISK AND LIQUIDITY ON THE PROFITABILITY OF ISLAMIC COMMERCIAL BANKS - Dewi, Nurmila (HEI EMA : Jurnal Riset Hukum, Ekonomi Islam, Ekonomi, Manajemen dan Akuntansi, 2024)
This study aims to investigate how Indonesian Islamic commercial banks' profitability, measured by Return on Assets (ROA), is affected by Non-Performing Financing (NPF), Capital Adequacy Ratio (CAR), and Financing to Deposit Ratio (FDR). Panel data regression analysis was used as a quantitative approach in this study. Purposive sampling was used to choose the sample, which comprised Islamic commercial banks registered with the Financial Services Authority (OJK). Five Islamic commercial banks with a total of 80 observations throughout the 2021–2023 period were selected based on the specified criteria. Secondary data from Islamic Banking Statistics, quarterly financial statements, and other relevant literature was used. EViews software was used to analyze data using the Fixed Effect Model (FEM). The results show that the profitability of Indonesia's Islamic commercial banks is significantly impacted concurrently by NPF, CAR, and FDR. ROA is significantly impacted negatively by NPF and CAR and positively by FDR. The research model appears to adequately account for variations in the profitability of Islamic banks, as indicated by the Adjusted R-squared value of 96.7%. These findings imply that controlling financing risk, guaranteeing capital sufficiency, and monitoring liquidity are essential components for improving the financial performance of Indonesia's Islamic commercial banks.